A RARE DISEASE OF THE BREAST: BOWEN’S DISEASE - Yazicioglu, Murat B; Tokyol, Cidem; Turel, kadir S; Keskin, Ahmet I; Aktepe, Fatma (National Journal of Medical Research, 2014)
Bowen’s disease (BD) or in situ squamous cell carsinoma of skin is a malign lesion restricted to the epidermis without evidence of dermal invasion. Etiological factors for BD include ultraviolet light, human papillomavirus, immunosuppression and carcinogen agents such as arsenic. It’s frequently seen in sun-exposed areas of skin such as head, body and extremity, but other sites for example genital areas can also be affected. Bowen’s disease of the nipple is extremely rare. We report a case with Bowen’s disease of nipple and discuss therapeutic implications and the importance of immunohistochemistry in the diagnosis of Bowen’s disease.